Postoperative Changes in the Distal Residual Aorta after Surgery for Acute Type A Aortic Dissection: Impact of False Lumen Patency and Size of Descending Aorta - Leontyev, Sergey; Haag, Felix; Davierwala, Piroze M.; Lehmkuhl, Lukas; Borger, Michael A.; Etz, Christian D.; Misfeld, Martin; Gutberlet, Matthias; Mohr, Friedrich W. (The Thoracic and Cardiovascular Surgeon, 2017)
Objective In the present study, we retrospectively identified and analyzed the factors that influenced progressive dilatation of the residual distal aorta after surgical repair for acute type A aortic dissection (acute type A).Methods A total of 477 patients underwent surgical repair for acute type A aortic dissection between 1995 and 2012. Postoperative and follow-up computed tomography (CT) scans of the descending aorta were available in 105 patients. We analyzed the maximum aortic diameter, total luminal area, and true luminal area of the descending thoracic and abdominal aorta.Results The mean follow-up time was 4.5 ± 3 years, and the mean time interval between CT scan investigations was 2.0 ± 2.3 years. A residual dissection membrane was observed in 80 (76%) patients, with presence of a patent false lumen (FL) in 52 patients (50%) and a thrombosed FL in 28 patients (26%).Progression of aortic disease with an increase in aortic diameter greater than 10 mm was observed in 14.3% (n = 15) of patients during follow-up. The independent predictors that influenced progressive dilation of the descending aorta by 10 mm or more were postoperative descending aortic diameter greater than 40 mm (p = 0.006; odds ratio [OR], 5.6; 95% confidence interval [CI], 1.6–19) and postoperative patent FL (p = 0.002; OR, 8.5; 95% CI, 2.2–32.3).The unadjusted 1- and 5-year freedom from reoperation was 96.9 ± 2 and 80.1 ± 5%, respectively. Marfan syndrome (p = 0.006; OR, 5.2; 95% CI, 1.6–16.9) and postoperative descending aortic diameter greater than 40 mm (p = 0.07; OR, 4.1; 95% CI, 1.4–11.6) were independent predictors of aorta-related reoperations.The mean survival at 1, 5, and 8 years was 90.7 ± 3, 82.5 ± 4, and 70 ± 6%, respectively. Previous cardiac surgery was independent predictor of midterm survival (hazard ratio, 3.6; 95% CI, 1.03–2.8; p = 0.04).Conclusions A regular follow-up CT scan is mandatory to assess progressive dilatation of the distal residual aortic arch, descending thoracic, and abdominal aorta after surgical repair of acute type A dissection, particularly in patients with a patent FL, descending aortic diameter greater than 40 mm, and/or Marfan syndrome.
Keywords: type A aortic dissection; follow-up CT scan; progressive dilatation